FACTORS ASSOCIATED WITH THE INCIDENCE OF MICROALBUMINURIA AND LEFT VENTRICULAR HYPERTROPHY IN HYPERTENSIVE SUBJECTS - Suhrawarni Suhrawarni (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACTMicroalbuminuria (MA) and Left Ventricular Hypertrophy (LVH) are as independent predictor to cardiovascular morbidity and mortality in Hypertensive (HT) patients. Hipertension causes target organ damage such as LVH and chronic kidney disease. Microalbuminuria one of the earliest indications of kidney injury in patients with HT. Left Ventricular Hypertrophy is adaptation process to maintain the stability of the contraction function, but will be a pathological process. The pathogenesis relationship between MA and LVH in essential HT is unclear. The presence of MA and LVH in HT show the high risk for cardiovascular events. This study aimed to knows the factors that contribute the incidence of MA and LVH in HT patients. Using observational study with cross sectional design in HT subjects, at Wahidin Sudirohusodo Hospital, aged over 18 years old. Measuring of Body mass index were performed on all study subjects, MA refers to an abnormally increased excretion rate of albumin in the urine and Echocardiography examination used to evaluation of LVH. This study showed Obesity influence the incidence of LVH in HT subject. Key words: Microalbuminuria, Left Ventricular Hypertrophy, Hypertension.